PTEN Methylation Promotes Inflammation and Activation of Fibroblast-Like Synoviocytes in Rheumatoid Arthritis - Li, Xiao-Feng; Wu, Sha; Yan, Qi; Wu, Yuan-Yuan; Chen, He; Yin, Su-Qin; Chen, Xin; Wang, Hua; Li, Jun (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is characterized by a tumor-like expansion of the synovium and the subsequent destruction of adjacent articular cartilage and bone. Our early research has proved that phosphatase and tension homolog deleted on chromosome 10 (PTEN) contributes to the activation of fibroblast-like synoviocytes (FLS) in adjuvant-induced arthritis (AIA), however, the precise epigenetics methylation was unclear in RA FLS. In this study, we found PTEN was down-regulated, while DNMT1 up-regulated in human RA and rat AIA FLS. The ChIP and MSP assay has clearly detected the DNA methylation of PTEN increased in RA FLS with TNF-α. Moreover, 5-Aza also suppressed the inflammation, chemokines and activation of FLS and paws swelling in vitro and in vivo. Interestingly, over-expression of PTEN reduced inflammation and activation of FLS by AKT pathway in RA. Consistently, Intra-articular injection of ad-PTEN in AIA knees dramatically reduced inflammatory and paw swelling in vivo. Thus, our findings suggested that DNA methylation of PTEN promotes the of inflammation and activation of FLS in RA.